Police conflict management, Volume II: training and education - Staller, Mario; Körner, Swen; Zaiser, Benni (Palgrave Macmillan, 2023)
Chapter 1: Training and Education for Police Conflict Management -- Chapter 2: Criteria for High Quality Training of Police Officers -- Chapter 3: Empowering police trainers: Introducing the costraints-led approach for the design of effective learning environments in police training -- Chapter 4: Coaching Police Conflict Management -- Chapter 5: Sport Psychology Applied to Tactical Training of Law Enforcement Officers -- Chapter 6: Moral Injury as a Challenge in a Value-driven Profession- Insights from Ethics for the Education and Training of Police Agents -- Chapter 7: Martial arts myths in police use-of-force training -- Chapter 8: Police checks and arrests escalating into conflict: Coping principles and strategies taught in Swiss police academics drawn from research in social psychology -- Chapter 9: How officers perform and grow under stress: Police training in virtual reality -- Chapter 10: Trialogic interventions: An innovative anti-stigma module for de-escalation trainings -- Chapter 11: An Evidence-Informed Approach to De-escalation Training -- Chapter 12: De-escalation Fundamentals -- Chapter 13: Police Hostage and Crisis Negotiation Training: Foci, Protocols and Best Practice Principles -- Chapter 14: Tactical Gaze Control and Visual Attention in Law Enforcement -- Chapter 15: Professional Shooting Tests in South Africa: A Qualitative-Descriptive Study and Critique -- Chapter 16: Police Training and Police Violence in Scandinavia -- Chapter 17: Leadership as a mental shield: How leaders of specialised police units promote inner resilience and mental stability.